Analysis of Financial Performance Impact to Expected Return on listed bank (Period 2009-2017) - Zakchona, Elia; Sihombing, Pardomuan (Journal of Entrepreneurship, Management and Industry (JEMI), 2019)
This research aims to analyze the relationship between financial performance to expected return in bank sector listed on Indonesian stock exchange (BEI) in 2009 – 2017, by partial and simultaneous equation model. The research population was limited to banking sector and research’s sample was used to sampling based on the total of biggest assets from 11 banks. This research used panel data model with regression analysis on E-views 10 programme to gauge the impact of independent variables (Capital Adequacy Ratio, Non-Performing Loan, Net Interest Margin, Return on Assets, Loan to Deposit Ratio, Debt to Equity Ratio, and Price to Book Value) to the dependent variable (expected return). The results showed that CAR, NPL, NIM, ROA, DER, LDR, and PBV ratios have significant and positive impacts on expected return by simultaneous equation model. In partial equation model, CAR, NPL, NIM, and ROA ratios have not significant and have positive impacts on expected return. DER’s ratio has significant and positive impact on expected return. LDR and PBV ratios have significant and negative impacts on expected return.